Abnormal vaginal bleeding in women with venous thromboembolism treated with apixaban or warfarin - Brekelmans, Marjolein P.A.; Scheres, Luuk J.J.; Bleker, Suzanne M.; Hutten, Barbara A.; Timmermans, Anne; Büller, Harry R.; Middeldorp, Saskia (Thrombosis and Haemostasis, 2017)
Abnormal vaginal bleeding can complicate direct oral anticoagulant (DOAC) treatment. We aimed to investigate the characteristics of abnormal vaginal bleeding in patients with venous thromboembolism (VTE) receiving apixaban or enoxaparin/warfarin. Data were derived from the AMPLIFY trial. We compared the incidence of abnormal vaginal bleeding between patients in both treatment arms and collected information on clinical presentation, diagnostic procedures, management and outcomes. In the AMPLIFY trial, 1122 women were treated with apixaban and 1106 received enoxaparin/warfarin. A clinically relevant non-major (CRNM) vaginal bleeding occurred in 28 (2.5 %) apixaban and 24 (2.1 %) enoxaparin/warfarin recipients (odds ratio [OR] 1.2, 95 % confidence interval [CI] 0.7–2.0). Of all CRNM bleeds, 28 of 62 (45 %) and 24 of 120 (20 %) were of vaginal origin in the apixaban and enoxaparin/warfarin group, respectively (OR 3.4; 95 % CI 1.8–6.7). Premenopausal vaginal bleeds on apixaban were characterised by more prolonged bleeding (OR 2.3; 95 %CI 0.5–11). In both pre- and postmenopausal vaginal bleeds, diagnostic tests were performed in six (21 %) and in seven (29 %) apixaban and enoxaparin/ warfarin treated patients, respectively. Medical treatment was deemed not necessary in 16 (57 %) apixaban and 16 (67 %) enoxaparin/warfarin recipients. The severity of clinical presentation and course of the bleeds was mild in 75 % of the cases in both groups. In conclusion, although the absolute number of vaginal bleeding events is comparable between apixaban and enoxaparin/warfarin recipients, the relative occurrence of vaginal bleeds is higher in apixaban-treated women. The characteristics and severity of bleeding episodes were comparable in both treatment arms.
Keywords: Anticoagulants; apixaban; warfarin; venous thromboembolism; abnormal; vaginal bleeding